HUBUNGAN AKTIVITAS FISIK DENGAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS BINJAI ESTATE - Elfira, Eqlima; Faswita, Wirda (NHM PRESS, 2023)
Diabetes Mellitus (DM) is a very dangerous disease, because it can cause complications. The survey on people with diabetes mellitus from 2019 to 2020 was 1227 cases. Successful management of diabetes mellitus can be achieved through physical activity, and balanced with adherence to taking anti-diabetic drugs as a form of pharmacological intervention. The purpose of this study was to determine the relationship between physical activity and blood sugar levels in patients with type 2 diabetes mellitus at the Binjai Estate Health Center. The design of this study was cross-sectional with purposive sampling technique on 20 respondents. Data collection method using Baecke Questionnaire. Analysis using the chi square test with α = 0.05. The results of the analysis showed that there were 10 people (50%) with abnormal blood sugar levels with light physical activity, 3 people (15%) with normal sugar levels and 3 people (15%) with abnormal sugar levels having moderate physical activity, 2 people (10%) with normal blood sugar levels and 2 people (10%) with abnormal blood sugar levels had heavy physical activity. With the result value 6.667a df 2 and the value of Asymp.Sig. (2-sided) = 0.036 < = 0.05 which means this means that there is a relationship between physical activity and blood sugar levels in Type 2 Diabetes Mellitus Patients at the Binjai Estate Health Center in 2020. It is recommended for people with diabetes mellitus to always be active in doing activities. Physical activity.